Itinéraires sociologiques - Lévesque, Georges-Henri; Poulin, Gonzalve; Falardeau, Jean-Charles; Dion, Léon; Bergeron, Gérard; Lacoste, Norbert; Rocher, Guy; Garigue, Philippe; Dumont, Fernand; Fortin, Gérald; Tremblay, Marc-Adélard; Szabo, Denis; et al. (Recherches sociographiques)

(untitled) (Département de sociologie, Faculté des sciences sociales, Université Laval, 1974)
Itinéraires sociologiques